(untitled) (Iranian Journal of Kidney Diseases, 2012)
Membranoproliferative glomerulonephritis (MPGN) is characterized by proliferation of mesangial and endothelial cells and by thickening of the peripheral capillary walls. Type II of the MPGN is associated with complement abnormalities which are factor H deficiencies due to mutations in the complement factor H (CFH) gene. We report a 15-year-old boy diagnosed with MPGN II in whom genetic analyses of the CFH gene revealed that the patient was heterozygote for a polymorphism in exon 2 of the CFH (c.184G>A), heterozygote for a polymorphism in exon 9 of the CFH (c.1204C>T), and heterozygote for a polymorphism in exon 10 of the CFH (c.1419G>A). These data recapitulate a prototypical complement genetic profile, the presence of major risk factors for MPGN II, which support the hypothesis that these dense deposit diseases have a common pathogenic mechanism involving dysregulation of the alternative pathway of complement activation.